The Relationship between Odorrana hosii Skin Histology and Habitat Water Quality in Different Locations of Sarawak - AHMAD HATA, RASIT; VIVIAN, THAM; RAMLAH, ZAINUDIN; MOHAMMAD ZULKARNAEN, AHMAD NARIHAN (UNIMAS Publisher, 2023)
Recent study has revealed that the poison gland in Odorrana hosii skin act as defensive mechanism and can help in wound healing management of a frog species. Since skin is the first organ that come into contact with the surrounding, the habitat of the species should be related to the properties of the frogs’ skin. Thus, we investigated the O. hosii skin histology in relation to water quality parameters at different localities in Sarawak. The goal of study is to uncover a link between O. hosii habitat and its skin histology at four different locations: Ranchan Recreational Park (RRP), Matang Wildlife Centre (MWC), Borneo Highlands (BH), and Santubong National Park (SNP). The water quality criteria for each area were pH, turbidity, temperature, and dissolved oxygen (DO). The results showed that DO concentration of the habitat is the most essential element in affecting the health of the amphibian skin, as well as the forested areas (MWC, SNP, and BH) that protect the skin from direct sunlight. The DO of the habitat differed significantly for the mean number of mucous and seromucous glands at 0.01 (α = 0.05) and 0.03 (α = 0.05), respectively. The number of mucous glands and DO were found to have a strong positive correlation at 0.701. However, the number of seromucous glands showed a strong negative correlation with DO at -0.623. O. hosii skin from the four different localities was found to have cutaneous gland variations that reflect the environment in the number of glands. Mucous glands play an important role in indicating the localities’ water quality, which reflects adaptation of O. hosii to its habitat. This highlights the importance of preserving natural habitats for this sensitive species. Keynote: Bornean frog, histology, Odorrana hosii, skin, water quality